Runaway blue main-sequence stars at high Galactic latitudes: Target selection with Gaia and spectroscopic identification - Raddi, Roberto; Irrgang, Andreas; Heber, Ulrich; Schneider, David; Kreuzer, Simon (Astronomy & Astrophysics, 2021)
Context. The ESA Gaia mission is a remarkable tool for stellar population analysis through its accurate Hertzsprung-Russell diagram. Its precise astrometry has propelled detailed kinematic studies of the Milky Way and the identification of high-velocity outliers. Aims. Motivated by the historical identification of runaway main-sequence (MS) stars of an early spectral type at high Galactic latitudes, we test the capability of Gaia at identifying new such stars. Methods. We selected ≃2300 sources with Gaia magnitudes of GBP-GRP ≤ 0.05, which are compatible with the colors of lowextinction MS stars that are earlier than a mid-A spectral type, and obtained low-resolution optical spectroscopy for 48 such stars. By performing detailed photometric and spectroscopic analyses, we derived their atmospheric and physical parameters (effective temperature, surface gravity, radial velocity, interstellar reddening, spectrophotometric distance, mass, radius, luminosity, and age). The comparison between spectrophotometric and parallax-based distances enabled us to disentangle the MS candidates from older blue horizontal branch (BHB) candidates. Results.We identify 12 runaway MS candidates, with masses between 2 and 6 M⊙. Their trajectories were traced back to the Galactic disk in order to identify their most recent Galactic plane crossings and the corresponding flight times. All 12 candidates are ejected from the Galactic disk within 2 to 16.5 kpc from the Galactic center and possess flight times that are shorter than their evolutionary ages, which is compatible with a runaway hypothesis. Three MS candidates have ejection velocities exceeding 450 km s-1, thus, they appear to challenge the canonical ejection scenarios for late B-type stars. The fastest star of our sample also has a non-negligible Galactic escape probability if its MS nature can be confirmed.We identify 27 BHB candidates, and the two hottest stars in our sample are rare low-mass stars of late O- A nd early B-types, evolving towards the white dwarf cooling sequence. Conclusions. The combination of Gaia parallaxes and proper motions can lead to the efficient selection of runaway blue MS candidates up to 10 kpc away from the Sun. High resolution spectra are needed to confirm the MS status, via precise measurements of projected rotational velocities and chemical compositions.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: Early-type; Stars: Fundamental parameters; Stars: Horizontal-branch; Stars: Kinematics and dynamics